1970
DOI: 10.36902/sjesr-vol4-iss2-2021(477-482)
|View full text |Cite
|
Sign up to set email alerts
|

Female Prisoners in Sindh: A Health Analysis for Policy Makers

Abstract: Unfortunately, the self-reported health status of female prisoners in Pakistan and especially in Sindh province have not been appropriately explored or documented. No doubt, the health of female prisoners is more vulnerable as compared to male prisoners. However, neither policymakers nor social scientists paid attention to the health-related issues of female prisoners in Pakistan. Therefore, 113 (convicted: 28, under trial: 85) female prisoners in three prisons of Sindh (Karachi, Hyderabad, and Larkana) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
0
Order By: Relevance
“…The lack of privacy for women in prisons extends beyond the physical infrastructure, such as inadequate bathing and toilet facilities. Avais et al (2021) have fingered at maximum jails providing prisoners with no safe and health water. Mushtaq and Yasin (2021) found that the hygienic condition in Pakistani jails is below the standardized line as compared to the rest of the countries.…”
Section: A Jailed Mother Sharedmentioning
confidence: 99%
“…The lack of privacy for women in prisons extends beyond the physical infrastructure, such as inadequate bathing and toilet facilities. Avais et al (2021) have fingered at maximum jails providing prisoners with no safe and health water. Mushtaq and Yasin (2021) found that the hygienic condition in Pakistani jails is below the standardized line as compared to the rest of the countries.…”
Section: A Jailed Mother Sharedmentioning
confidence: 99%